Asymptotic expansion at infinity of solutions of Monge–Ampère type equations. (November 2021) - Liu, Zixiao; Bao, Jiguang
Abstract: We obtain a quantitative expansion at infinity of solutions for a kind of Monge–Ampère type equations that origin from mean curvature equations of Lagrangian graph ( x, D u ( x ) ) and refine the previous study on zero mean curvature equations and the Monge–Ampère equations.